Visum ET Repertum Sebagai Alat Bukti Dalam Tindak Pidana Pembunuhan Berencana - Sahali, Gustilawati; Puluhulawa, Fenty U.; Mantali, Avelia Rahmah Y. (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
In the process of investigating a crime of ordinary or premeditated murder, it is necessary to have evidence to prove that the crime has been committed. One of the means of evidence referred to is regulated in Law no. 8/1981 is Expert Statement in written form, in this case it is Visum et Repertum. Visum et Repertum is a written report made by a doctor or other forensic expert that contains what they found on the victim's body. However, Visum et Repertum usually differs from what actually happened and also from the testimony of the accused that was previously made. This research was conducted using a descriptive research type with normative-empirical legal research. The role of Visum et Repertum is to explain to Judges and Investigators regarding the preparation and planning of crimes committed by the suspect beforehand by looking at the instructions written in the Visum et Repertum; for example time of death, cause of death, type of injury to the victim, and so on. Visum et Repertum can be replaced or re-examined if the results received do not provide sufficient information to the Judge. Meanwhile, the testimony of the defendant can be rejected if the Judge knows that it is a false statement or does not match other evidence.